Simultaneous mapping of unevenly distributed tissue hypoxia and vessel permeability in tumor microenvironment. (19th December 2016) - Oda, Keitaro; Iwamoto, Yuichiro; Tsukada, Kosuke
Abstract: New blood vessels that form within tumors undergo repeated irregular divergence, joining, and twisting, resulting in blood vessels with abnormal tissue distribution, structure, and function. Tumor vessels exhibit increased spatially uneven permeability and oxygen delivery, characteristics that may reduce the efficacy of radiotherapy and chemotherapy. Therefore, it is vital to establish technologies for quantitatively mapping hypoxia and vessel permeability within tumors to clarify tumor mechanisms. However, existing methods can only acquire mean measurements within a given region or the entire tissue, and there have been no reports of technologies for measuring permeability at multiple points in individual vessels or for simultaneously performing oxygen partial pressure mapping. Here, new blood vessels formed within tumors were detected on fluorescent blood flow images, and measurement points were set at fixed intervals across individual blood vessels. Fluorescent dye that leaked out over time was excited with a continuous wave optical laser to calculate the permeability distribution of individual vessels. On the other hand, an oxygen probe dye was excited with a pulse laser and oxygen concentration-dependent light emission was analyzed to map oxygen partial pressure. Oxygen partial pressure imaging in tumors transplanted onto the backs of mice showed that tissue regions surrounding minute tumor vessels were generally hypoxic. Furthermore, compared with the normal dermal vasculature, there was greater variation in vessel permeability, and sites with very high vessel permeability were detected. We designed a system for high-resolution spatial mapping of blood vessel permeability and tissue oxygenation in tumor microvasculatures, thereby clarifying the relationship between local hypoxia and vessel permeability. It is anticipated that these findings could be applied to improve anticancer drug delivery and radiotherapy by identifying the dependence of local tissue oxygenation on the vessel structure and hemodynamics.